Pelatihan Manajemen Risiko dan Kelanjutan Usaha bagi UMKM di Provinsi Banten - Sev Rahmiyanti; Rini Widianingsih; Donny Indradi; Achmad Fauzi; Frida Tri Meidina; Sabrina Natasya Putri Bachtiar; Yudistira Bangkit Sanjaya Bachtiar (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
Entrepreneurship training activities organized by the Banten Province Cooperatives and SMEs Service are a strategic step in increasing the capacity of Micro, Small, and Medium Enterprises (MSMEs). The training, which was held on June 24-25, 2025, was attended by 50 business actors and focused on risk management and was interested in business. Through the delivery of material from professional speakers, participants are expected to be able to implement effective and sustainable business management strategies. The results of the training show that a good understanding of business management can help MSMEs maintain business stability and growth. In addition, this training also offers an understanding of the importance of innovation and adjustment in facing the challenges of a changing market. Through improving skills and knowledge, it is hoped that MSMEs can be better prepared to face challenges and take advantage of existing opportunities, so that they can contribute to local and national economic growth.